ACTIVITATEA ORGANIZAȚIILOR INTERNAȚIONALE ÎN GESTIONAREA CRIZEI COVID-19 - Cebotari, Svetlana (Academia de Administrare Publică, Republica Moldova, 2021)
One of the most discussed issues in academia, but also in the discourse of polemologists, political scientists, economists and specialists in other fields is the issue regarding the impact of the COVID-19 virus on international security. Although all the attention of the international community has been focused on the emergence of the COVID-19 virus and its impact on the individual, societal, human and interpersonal relationships, it is worth paying attention to the involvement of international organizations in managing the COVID-19 crisis.This article aims to highlight the role and involvement of international organizations in managing the COVID-19 crisis. The involvement of the United Nations, specifically of the UN Security Council, in the management of issues related to the COVID-19 crisis will be examined. The activity of the World Health Organization, the European Union, the North Atlantic Alliancein the management of the COVID-19 pandemic will also be examined.
THE ACTIVITY OF INTERNATIONAL ORGANIZATIONS IN COVID-19 CRISIS MANAGEMENT
ДЕЯТЕЛЬНОСТЬ МЕЖДУНАРОДНЫХ ОРГАНИЗАЦИЙ В УПРАВЛЕНИИ КРИЗИСОМ COVID-19
Keywords: United Nations; UN Security Council; World Health Organization; European Union; North Atlantic Alliance; Covid-19